Simultaneous quantification of propofol, ketamine and rocuronium in just 10 μL plasma using liquid chromatography coupled with quadrupole mass spectrometry and its pilot application to a pharmacokinetic study in rats. (17th April 2019) - Shopova, Teodora; Kiefer, Daniel; Wolf, Beate; Maurer, Felix; Sessler, Daniel I.; Volk, Thomas; Fink, Tobias; Kreuer, Sascha
Abstract: The combination of propofol, ketamine and rocuronium can be used for anesthesia of ventilated rats. However, reliable pharmacokinetic models of these drugs have yet to be developed in rats, and consequently optimal infusion strategies are also unknown. Development of pharmacokinetic models requires repeated measurements of drug concentrations. In small animals, samples must be tiny to avoid excessing blood extraction. We therefore developed a drug assay system using high‐performance liquid chromatography coupled with quadrupole mass spectrometry that simultaneously determines the concentration of all three drugs in just 10 μL rat plasma. We established a plasma extraction protocol, using acetonitrile as the precipitating reagent. Calibration curves were linear with R 2  = 0.99 for each drug. Mean recovery from plasma was 91–93% for propofol, 89–93% for ketamine and 90–92% for rocuronium. The assay proved to be accurate for propofol 4.1–8.3%, ketamine 1.9–7.8% and rocuronium −3.6–4.7% relative error. The assay was also precise; the intra‐day precisions were propofol 2.0–4.0%, ketamine 2.7–2.9% and rocuronium 2.9–3.3% relative standard deviation. Finally, the method was successfully applied to measurement the three drugs in rat plasma samples. Mean plasma concentrations with standard deviations were propofol 2.0 μg/mL ±0.5%, ketamine 3.9 μg/mL ±1.0% and rocuronium 3.2 μg/mL ±0.8% during ventilation.